2016
DOI: 10.1038/nature20126
|View full text |Cite
|
Sign up to set email alerts
|

Self-bound droplets of a dilute magnetic quantum liquid

Abstract: Self-bound many-body systems are formed through a balance of attractive and repulsive forces and occur in many physical scenarios. Liquid droplets are an example of a self-bound system, formed by a balance of the mutual attractive and repulsive forces that derive from different components of the inter-particle potential. It has been suggested 1, 2 that self-bound ensembles of ultracold atoms should exist for atom number densities that are 10 8 times lower than in a helium droplet, which is formed from a dense … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
485
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 534 publications
(504 citation statements)
references
References 27 publications
18
485
1
Order By: Relevance
“…The observability of microscopic quantum effects involving a substantial fraction of the particles in a coherent macroscopic setting generally requires going beyond MF, for example, at low density in one dimension (1D) [1,2] or high density in three dimensions (3D). In 3D systems, the high-density Lee-Huang-Yang corrections, which are induced by quantum correlations, were realized experimentally using the Feshbach resonance [3] and in the spectacular form of "quantum droplets" in dipolar [4][5][6] and isotropic [7] bosonic gases, i.e., as self-trapped states stabilized against the collapse by the beyond-MF selfrepulsion. This stabilization was predicted in Refs.…”
mentioning
confidence: 99%
“…The observability of microscopic quantum effects involving a substantial fraction of the particles in a coherent macroscopic setting generally requires going beyond MF, for example, at low density in one dimension (1D) [1,2] or high density in three dimensions (3D). In 3D systems, the high-density Lee-Huang-Yang corrections, which are induced by quantum correlations, were realized experimentally using the Feshbach resonance [3] and in the spectacular form of "quantum droplets" in dipolar [4][5][6] and isotropic [7] bosonic gases, i.e., as self-trapped states stabilized against the collapse by the beyond-MF selfrepulsion. This stabilization was predicted in Refs.…”
mentioning
confidence: 99%
“…Scientists have made other surprising observations, like magnetic liquid droplets that fall like solid rocks, or neutral particles that act like they carry a charge (4,5). Under certain conditions, BECs can be controlled to form swirling vortices, or explode like This velocity-distribution data for a gas of rubidium atoms confirmed the discovery of the Bose-Einstein condensate in 1995.…”
mentioning
confidence: 69%
“…To analyse the previous expression forĤ I , we denote by p a general function of theâ's operators entering in (64). In general the terms V p12 V 2 p12−pÂp and V p12 V 2 p12+pÂp are different.…”
Section: Potential As a Sum Of Terms With 2 Factorsmentioning
confidence: 99%
“…On the other hand, the presence of an asymmetric harmonic trapping in combination with short-range repulsive interactions can eliminate such instabilities, opening the way to the study of interesting many-body physics with long-range interactions [59,60]. Recent experiments with dipolar BECs showed that under certain conditions where instability is expected from a standard Bogoliubov approach, dense clusters with many atoms can occur [61][62][63][64][65], which are expected to be superfluid [66]. Two interpretations have been proposed to explain the stabilization of this phase, namely the presence of weak 3-body interactions [11,12] and beyond mean-field effects (Lee-Huang-Yang type corrections) [67][68][69].…”
Section: B Dipolar Interactions In Magnetic Atoms and 3-body Contactmentioning
confidence: 99%